2013
DOI: 10.1007/s00247-013-2713-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a cartoon and photograph montage storybook in preparing children for voiding cystourethrogram

Abstract: The cartoon and photograph montage storybook format of preparing children for VCUG was effective in increasing their tolerance for the procedure. The storybook should be mailed out in advance because the majority of families did not pursue information on preparing their children for VCUG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…We believe that in addition to distraction, understanding the injection process can reduce the fear and uncertainty of preschool‐aged children. Although some picture books have been used to describe the medical procedures to children (Bemelmans, ; Gebarski et al, ; Ono, Oikawa, Hirabayashi, & Manabe, ; Rey & Rey, ), to our knowledge, the process of venipunctures has not been explained for preschool‐aged children. An appropriate venipuncture picture book that adequately conveys information can be used for preschool‐aged children when receiving the medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that in addition to distraction, understanding the injection process can reduce the fear and uncertainty of preschool‐aged children. Although some picture books have been used to describe the medical procedures to children (Bemelmans, ; Gebarski et al, ; Ono, Oikawa, Hirabayashi, & Manabe, ; Rey & Rey, ), to our knowledge, the process of venipunctures has not been explained for preschool‐aged children. An appropriate venipuncture picture book that adequately conveys information can be used for preschool‐aged children when receiving the medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We highlighted the ability of the preschool‐aged children, particularly aged 3 to 6 years, to maintain the required attention and to reliably relate the nurse's or doctor's injection of the drug into the vein with the picture book content. Studies have shown positive effects of picture books on decreasing the behavioural distress of children receiving medical treatment; for example, children prepared for a voiding cystourethrogram using a storybook had less distress than those who did not use a storybook (Gebarski et al, ). A picture book titled The Tale of Woody's Tonsils was found to be effective in decreasing preoperative anxiety and particularly effective for girls and children in the 7‐year age group (Tunney & Boore, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,101,102 A cartoon and photograph montage storybook about VCUG procedures can reduce both patients' and parents' anxiety. 103 If children know more about painful procedures, they feel less distress than those who do not know the details. 104 It is important to include specialists with much experience in child development, education, and psychosocial care of children and families receiving painful medical care, such as VCUG.…”
Section: Non-pharmacological Therapymentioning
confidence: 99%
“…Starting in the early 2000s, studies have shown that bibliotherapy can be an effective tool for educating children and their parents. Gebarski and colleagues reported that children who were prepared with a montage storybook explaining a voiding cystourethrogram exhibited significantly less distress during and after the procedure than those not given the storybook . Leung and colleagues demonstrated that, after a single read‐through of a comic‐style storybook promoting good nutritional choices, minority youth were more than three times as likely to choose a healthy snack as youth not given the storybook .…”
Section: Introductionmentioning
confidence: 99%